If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + -1)(2x + -1) = 18 Reorder the terms: (-1 + 2x)(2x + -1) = 18 Reorder the terms: (-1 + 2x)(-1 + 2x) = 18 Multiply (-1 + 2x) * (-1 + 2x) (-1(-1 + 2x) + 2x * (-1 + 2x)) = 18 ((-1 * -1 + 2x * -1) + 2x * (-1 + 2x)) = 18 ((1 + -2x) + 2x * (-1 + 2x)) = 18 (1 + -2x + (-1 * 2x + 2x * 2x)) = 18 (1 + -2x + (-2x + 4x2)) = 18 Combine like terms: -2x + -2x = -4x (1 + -4x + 4x2) = 18 Solving 1 + -4x + 4x2 = 18 Solving for variable 'x'. Reorder the terms: 1 + -18 + -4x + 4x2 = 18 + -18 Combine like terms: 1 + -18 = -17 -17 + -4x + 4x2 = 18 + -18 Combine like terms: 18 + -18 = 0 -17 + -4x + 4x2 = 0 Begin completing the square. Divide all terms by 4 the coefficient of the squared term: Divide each side by '4'. -4.25 + -1x + x2 = 0 Move the constant term to the right: Add '4.25' to each side of the equation. -4.25 + -1x + 4.25 + x2 = 0 + 4.25 Reorder the terms: -4.25 + 4.25 + -1x + x2 = 0 + 4.25 Combine like terms: -4.25 + 4.25 = 0.00 0.00 + -1x + x2 = 0 + 4.25 -1x + x2 = 0 + 4.25 Combine like terms: 0 + 4.25 = 4.25 -1x + x2 = 4.25 The x term is -1x. Take half its coefficient (-0.5). Square it (0.25) and add it to both sides. Add '0.25' to each side of the equation. -1x + 0.25 + x2 = 4.25 + 0.25 Reorder the terms: 0.25 + -1x + x2 = 4.25 + 0.25 Combine like terms: 4.25 + 0.25 = 4.5 0.25 + -1x + x2 = 4.5 Factor a perfect square on the left side: (x + -0.5)(x + -0.5) = 4.5 Calculate the square root of the right side: 2.121320344 Break this problem into two subproblems by setting (x + -0.5) equal to 2.121320344 and -2.121320344.Subproblem 1
x + -0.5 = 2.121320344 Simplifying x + -0.5 = 2.121320344 Reorder the terms: -0.5 + x = 2.121320344 Solving -0.5 + x = 2.121320344 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.5' to each side of the equation. -0.5 + 0.5 + x = 2.121320344 + 0.5 Combine like terms: -0.5 + 0.5 = 0.0 0.0 + x = 2.121320344 + 0.5 x = 2.121320344 + 0.5 Combine like terms: 2.121320344 + 0.5 = 2.621320344 x = 2.621320344 Simplifying x = 2.621320344Subproblem 2
x + -0.5 = -2.121320344 Simplifying x + -0.5 = -2.121320344 Reorder the terms: -0.5 + x = -2.121320344 Solving -0.5 + x = -2.121320344 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.5' to each side of the equation. -0.5 + 0.5 + x = -2.121320344 + 0.5 Combine like terms: -0.5 + 0.5 = 0.0 0.0 + x = -2.121320344 + 0.5 x = -2.121320344 + 0.5 Combine like terms: -2.121320344 + 0.5 = -1.621320344 x = -1.621320344 Simplifying x = -1.621320344Solution
The solution to the problem is based on the solutions from the subproblems. x = {2.621320344, -1.621320344}
| a(a-2)=35 | | -25=-9+8m | | 6x+4=-8x-12 | | 66+x+1/2x+57=180 | | -x^2-.00091x+.00182=0 | | 7+4c+100e+e+3= | | 6x+4=8x-12 | | 4x-13=2x+25 | | 3/4x+8=14 | | (x+2)(x+2)=13 | | 0.24-0.03(x+3)=-0.03(1-x) | | 1/2t-3=7 | | 0.15/45 | | x+7x+4x= | | 8[1-(-4x-9)]=64x+152 | | ln(x^4)-ln(x^2)=3 | | 17+3*2-56/7 | | 3x-3=6x+3-3xt | | 3-3b=-3 | | 1/5+2/3z=1/3-3/4z | | 51-11x=15-7x | | -2n^2+13=0 | | (7x-12)+(5x+6)=90 | | 5x+7-2x=32-2x | | 18-r=14 | | 4(3n+4)=6(8n+1)+1 | | 12+17= | | -4(3+5m)-7=-38-m | | x-2/3=x/12+5/4 | | u-6/-2=-2 | | 2x+-2=6+4x | | 7x+53=3x+21 |